Design optimization on high-rise buildings considering occupant comfort reliability and joint distribution of wind speed and direction. (1st February 2018) - Fu, Jiyang; Zheng, Qingxing; Huang, Youqin; Wu, Jiurong; Pi, Yonglin; Liu, Qiongxiang
Highlights: Modal acceleration is used to assess occupant comfort instead of total acceleration. Mapping transformation and design point method are used to get frequency constraints. Failure probabilities are combined using joint probabilities of wind speed and direction. Abstract: A new procedure for the wind resistant optimization of high-rise buildings considering the uncertainties of the wind speed, structural natural frequency and damping ratio, and the joint distribution of the wind speed and direction is proposed. The novelty of the procedure includes three aspects. Firstly, the modal acceleration responses of buildings are employed to evaluate the occupant comfort in the building instead of the commonly used total acceleration responses. This enhances the applicability of the proposed method and reduces the computation error by including the effect of the reoccurrence period of wind and avoiding calculation of the peak factor of response. Secondly, because the current method such as the modified Hasofer-Lind-Rackwitz-Fiessler (HLRF) algorithm is not suitable to the optimization design considering multiple wind directions, to overcome this problem, the design point method in generalized random space (DPG method) is used to establish equations of reliability for converting modal acceleration constraints to natural frequency constraints, in which an approach of mapping transformation is used to treat the non-normal variables. Thirdly, by improving the method of determining the limit of the wind speed based on the joint distribution of the wind speed and direction, the failure probabilities of modal accelerations under all wind directions are combined based on the joint probability distribution of the wind speed and direction to obtain the limit of natural frequency constraints. The parameters of the joint probability distribution are determined from the meteorological observation data of the wind speed. In association with the Optimality Criterion (OC) algorithm, the proposed method is applied in the wind resistant optimization of a 60-stories standard model of Commonwealth Advisory Aeronautical Research Council (CAARC). The investigations show that the proposed method can effectively decrease the structural total weight subject to reliability frequency constraints, displacement constraints and inter-story drift constrains. Considering the randomness of parameters and joint distribution of the wind speed and direction in the comfort constraint could enhance the design space for the structural total weight.